2021
DOI: 10.15388/21-infor459
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Distance Learning Technologies by Teachers: Determining Factors and Emergency State Influence

Abstract: State of emergency affects many areas of our life, including education. Due to school closure during COVID-19 pandemic as a case of a long-term emergency, education has been moved into a remote mode. In order to determine the factors driving the acceptance of distance learning technologies and ensuring sustainable education, a model based on the Unified Theory of Acceptance and Use of Technology has been proposed and empirically validated with data collected from 550 in-service primary school teachers in Lithu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
(77 reference statements)
0
13
0
Order By: Relevance
“…Distance learning takes on different forms of communication, including synchronous and asynchronous interactions (Jevsikova et al, 2021). Synchronous sessions are live.…”
Section: Learning Management Systemsmentioning
confidence: 99%
“…Distance learning takes on different forms of communication, including synchronous and asynchronous interactions (Jevsikova et al, 2021). Synchronous sessions are live.…”
Section: Learning Management Systemsmentioning
confidence: 99%
“…For example, some scholars suggested that perceived risk, satisfaction, attitude, and trust should be considered to complement the original UTAUT model [37]. Other external factors have also been pointed out to influence teachers' use of new technologies in teaching, such as social networks, communication or exchanging information with peers, social media [38], organizational commitment [39], and teacher professional title promotion system [40]. Moreover, Zhang and Liu stressed that the impact of school reform and innovation policies, incentive measures, and teacher performance assessment mechanisms should be considered when analyzing the factors influencing teachers' application of new teaching methods and tools for professional development in a Chinese context [14].…”
Section: External Conditionsmentioning
confidence: 99%
“…Secondly, we assumed that the abovementioned factors affect teachers' instructional behavior directly and indirectly through teachers' intention to use ICT. Additionally, gender, working experience, and school level were considered the control variables because they were the significant moderators on the decision of ICT usage summarized by the prior researchers [31,39,43]. Therefore, Figure 1 depicts the initially hypothesized mechanism of the Chinese higher vocational college teachers' acceptance and usage of ICT in teaching.…”
Section: Hypothesized Model For the Current Studymentioning
confidence: 99%
“…Studies, such as Piramanayagam and Seal (2021) show that Performance Expectancy (PE), Effort Expectancy (EE), and facilitating Conditions (FC) greatly affect teachers' intention to use digital textbooks, respectively. In addition, several studies reported that teachers at elementary and other education levels have different levels of selfefficacy, belief, and perception (Balkaya and Akkucuk, 2021;Jevsikova et al, 2021). Based on this difference, it is necessary to analyze the factors affecting the intention of elementary school teachers to use digital textbooks.…”
Section: Introductionmentioning
confidence: 99%